ENTREPRENEURSHIP ATTITUDES AND MOTIVATIONS OF NIGERIAN STUDENTS - Osuagwu, Linus (APPS Publications, 2023)
This paper presents a comprehensive investigation into the entrepreneurship attitudes and motivations of Nigerian university students. Employing a descriptive research design, this study engaged in an extensive literature review, developed, and validated a tailored questionnaire, and analyzed responses from a diverse sample of students. The research reveals that Nigerian students exhibit a moderately low entrepreneurial attitude. Significantly, it uncovers that the primary motivation driving these students towards entrepreneurship is the allure of independence rather than financial incentives. The paper contributes theoretically by shedding light on the entrepreneurial inclinations within a developing country context, specifically Nigeria. It also extends the existing body of knowledge by highlighting the motivations and attitudes of Nigerian students towards entrepreneurship. These insights not only enrich academic discourse but also provide a basis for policy formulation and educational strategies aimed at nurturing entrepreneurship in Nigerian universities. The paper concludes with suggestions for future research, emphasizing the need to delve deeper into the factors influencing entrepreneurial attitudes in similar environments, especially developing countries.